Penerapan Biogas Dari Ampas Tahu Sebagai Pengganti Kayu Bakar Di Umkm Tahu Marina - Muara Jaya Simare Mare; Hazimah Hazimah (LPPM Universitas Putera Batam, 2019)
Utilization of renewable energy is very important to support for development in everyMicro Small Medium Enterprises. MSMEs Tahu Marina is one of the tofu-makingbusiness in batam since 2006 which has entered market share like some hotels, hospitals and traditional markets. This study aims to apply biogas from tofu pulp as a substitute for firewood which became one of the problems in MSMEs Tahu Marina. Strategic planning using Strength, Weaknesses, Opportunities, Threats (SWOT) methods to determine biogas implementation strategy. The results of the research can be a reference of the strategy of MSMEs Tahu Marina. From the results strategic planning of SWOT application of biogas in MSMEs Tahu Marina is in quadrant 1 (SO) with coordinate SW = 1.00 and OT = 1.02. in quadrant I is a favorable position, the application of biogas to MSMEs Tahu Marina has the power that can be used to exploit the opportunities that exist. The strategy undertaken is to develop new product to minimize non-permanent costs (firewood), utilize the waste as biogas feedstock build enough installations to meet the needs of steam combustion.